The Influences of Industry Internship, Career Guidance, and Working World Information to the Students Work Readiness of Grade XI SMK Palebon Semarang in Academic Year 2017/2018 - Purnama, N; Suryani, N; ., Sapuroh (KnE Social Sciences, 2018)
The aim of Vocational High School is to prepare students to be ready in entering working world. The objective of this study is to examine the influences of Industry Internship, career guidance, and working world information to the work readiness. The population of this research is students of Grade XI SMK Palebon Semarang. The total population of this research is 237 students from 6 classes with 149 students as the sample calculated by Slovin formula with 5% error rate. The data collection techniques use observation. interview. documentation. and questionnaire (questionnaire). The data analysis techniques use analysis of classical assumption test. multiple regression. hypothesis test. descriptive analysis fund percentage by using SPSS Program for Windows Release 23. The result of this research shows that multiple regression analysis obtained equation: Y = 5.866 + 0.119X1 + 0.246X2+ 0.203X3 + e. Simultaneously, industry Internship, career guidance, and working world information have positive and significant impact on work readiness for 46.6%. Parsially, Industry Internship affects 3.34%, career guidance affects 11.35%, and working world information affects 3.96% on the work readiness. The suggestion from this study is the industry internship place could thoroughly cover. For career guidance, the school could hold guidance program for preparing students to work after graduation so that they are more motivated and ready for facing working world. Further for working world information. the school could enhance working world information. Keywords: Industry Internship, Career Guidance, Working World Information and Work Readiness